Individual Psychological Characteristics of Individuals Engaged in Social Entrepreneurship - Romanova, Julia; Lisetska, Victoria (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The results of empirical research devoted to the study of individual psychological characteristics of individuals engaged in social entrepreneurship in Ukraine are considered in this article. Social entrepreneurship is a new area of practice that is developing rapidly but is still insufficiently studied in psychology. Foreign research projects compare social entrepreneurs’ personal traits with the ones of traditional entrepreneurs, members of the general public, employees in the same area of activity, volunteers, etc. There are such personal traits of social entrepreneurs that have a higher level of development (compared to others) as empathy, willingness to take risks and to cooperate and develop social networks, creativity, need for autonomy and independence, optimism, trust in others, belief in positive social changes, ability to cope with obstacles on their way to social mission implementation. Most researchers emphasize the developed sense of social responsibility, moral obligations towards others, self-sacrifice of social entrepreneurs. As a result of the empirical research of individual psychological characteristics of individuals engaged in social and traditional entrepreneurship in Ukraine psychological particularities within each group of entrepreneurs have been determined. A psychological portrait of social entrepreneur has been compiled based on the obtained empirical data: an active, focused on the external world, intent on reflection and introspection, receptive to obtain new knowledge, hardworking, creative, relatively emotionally stable, moderately conformable and ambitious individual, which is characterized by a high level of empathy and an internal locus of control, which can work successfully both as a team member and independently, which can adequately estimate their capabilities and make right decisions in situations of uncertainty and risk. The differences between groups of traditional and social entrepreneurs in such factors as «Openness» according to the Big 5 Personality Traits, «Сreative tendency», «Calculated risk-taking», «Internal locus of control» according to the General measure of Enterprising Tendency (GET) test, as well as according to the Balanced Emotional Empathy Test have been detected. Based on these findings one can conclude that a phenomenon of social entrepreneurship is a dynamic process that meets the urgent needs of society, corresponds to individual motives and is determined by the specifics of professional tasks we solve, and therefore by the type of business activity in general.